Not just things: the roles of objects at the end of life. Issue 4 (26th February 2018) - Cleeve, Helena; Tishelman, Carol; Macdonald, Alastair; Lindqvist, Olav; Goliath, Ida
Abstract: While the study of objects in care contexts is an emerging research field, it is largely overlooked in end of life (EoL) care. In this study, we empirically and inductively explore the roles of objects at the EoL from the perspective of bereaved family members. Open individual interviews were conducted with 25 family members recruited from palliative in‐patient and homecare units, as well as residential care facilities. After verbatim transcription, the interviews were analysed thematically. Based on these interviews, we conceptualise the roles of objects as relating to temporality, transformations of the everyday, and care. Through analysis we offer two main insights, the first relating to interdependency between objects and people, and the second to the recognition of objects as simultaneously flexible and stable in this interdependent relationship. The capacity and challenge of objects as part of EoL care lies in their ability to encompass various viewpoints and relationships simultaneously. This might provide valuable insights for staff caring for dying persons and their families. We propose that staff's ability to navigate objects in care practices could be meaningful in supporting the relationships between individuals in EoL situations.